Effect of high pressure processing on sugar‐snap cookie dough preservation and cookie quality. Issue 1 (18th July 2017) - Aguirre, A.; Karwe, M. V.; Borneo, R.
Abstract: In this study, cookie dough was subjected to high pressure processing (HPP) to evaluate the effect of this technology on the microbiological features and on the quality characteristics of both the dough and the cookies. HPP reduced the microbial counts of mesophilic bacteria and yeast/molds. Microbiological inactivation in the cookie dough was maintained for 7 days of storage at ambient temperature suggesting extended shelf‐life of the cookie dough. Cookie dough treated with HPP had higher density. Upon baking the spread rate of HPP treated dough was higher resulting in less baking time. The HPP cookie dough and the corresponding cookies made from them had darker tones compared to the untreated dough. Digital images of cookie surfaces showed that HPP cookies had smoother surface and tiny cracks which were evenly distributed. Practical applications: The utilization of high pressure for processing represents an opportunity to aid in the preservation and extension of self‐life of cereal products. Cookie dough, traditionally not preserved a room temperature, can be processed by high pressure and stored at ambient temperature. Cookies prepared with high pressured cookie dough spread faster during baking reducing total cooking time significantly, reducing, thus, processing time. Cookie quality characteristics are not significantly affected by high pressure processing.